Food waste as an index of foodservice quality - Ferreira, Maria (2013)
Purpose - The purpose of this paper is to evaluate waste at a Portuguese university setting in order to suggest improvements on foodservice sustainability. Design/methodology/approach - The work was developed during four weeks in order to allow the evaluation of parameters of an entire menu cycle. The index of waste/consumption (%) was obtained by the ratio between plate waste and the quantity of foods distributed, subtracting the weight of leftovers. Findings - The average index of waste/consumption was approximately 24 percent, higher in the days with a fish menu, values considered unacceptable. Each canteen user is served with approximately 940 g of foods, from which only 660 g were effectively consumed, corresponding to 80 g of leftovers and 200 g of waste. Originality/value - It seems possible and desirable to reduce food waste in order to optimize food unit profitability and sustainability. Reducing food waste will contribute to improve foodservice quality as well as consumer's satisfaction. Potential strategies to achieve this goal may include previous booking of meals, to adopt tray less during lunch and additionally analyze the eating patterns for a particular forecasted meal, and then prepare and serve food based on the appropriate forecast.